Propylthiouracil Induced p-ANCA+ Pyoderma Gangrenosum with Inflammatory Bowel Disease in Pregnancy - Budiyarto, Larasati; Mumtazah, Devi Arofah; Triatmoko, Sara Ester (Journal of Pakistan Association of Dermatologists, 2023)
Introduction: Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis characterized by painful ulcers with undermined edges and peripheral erythema. Global incidence of PG is estimated to be 3 to 10 cases per million people per year, affecting individuals aged between 25 to 54 years. Case Report: This case reports a 34-year-old female with deep painful ulcerous non-healing wounds on both legs which first appear on her pregnancy. Prolonged consumption of propylthiouracil (PTU) as treatment of hyperthyroidism was found. Gastrointestinal symptoms were denied. Histopathological examination revealed intense neutrophilic infiltration of dermis in skin biopsy and chronic ulcerative inflammation in ileum and colon biopsy. Result of p-ANCA was positive. Patient was diagnosed with pyoderma gangrenosum associated with drug-induced due to PTU use and inflammatory bowel disease. Combination therapy of systemic corticosteroid, two split-thickness skin graft (STSG) surgeries, oral dapsone, appropriate wound care, and management to eliminate predisposing factors resulted in favorable outcome. Conclusion : Pyoderma gangrenosum has been considered a challenging disease to diagnose and treat. It is important for clinicians to enhance knowledge of diagnosis and management of PG in order to yield a better prognosis. Keywords : inflammatory bowel disease, pregnancy, propylthiouracil, pyoderma gangrenosum, split-thickness skin graft surgery